2023
DOI: 10.1073/pnas.2206758120
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-specific transcriptomic signatures indicate neuroinflammation and altered neuronal activity in ASD temporal cortex

Abstract: Autism spectrum disorder (ASD) is a highly heterogeneous disorder, yet transcriptomic profiling of bulk brain tissue has identified substantial convergence among dysregulated genes and pathways in ASD. However, this approach lacks cell-specific resolution. We performed comprehensive transcriptomic analyses on bulk tissue and laser-capture microdissected (LCM) neurons from 59 postmortem human brains (27 ASD and 32 controls) in the superior temporal gyrus (STG) of individuals ranging from 2 to 73 years of age. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…The change of mitochondrial function, energy metabolism, EIF2 signaling, immune functions, ubiquitination, and DNA repair were found in global proteomics of peripheral blood‐derived lymphoblasts with homozygous HERC2 variants 117 . A transcriptome suggested that mitochondrial function, ribosome, and spliceosome components were down‐regulated in postmortem brain of ASD 118 …”
Section: Potential Pathogenesis Of Asdmentioning
confidence: 99%
See 3 more Smart Citations
“…The change of mitochondrial function, energy metabolism, EIF2 signaling, immune functions, ubiquitination, and DNA repair were found in global proteomics of peripheral blood‐derived lymphoblasts with homozygous HERC2 variants 117 . A transcriptome suggested that mitochondrial function, ribosome, and spliceosome components were down‐regulated in postmortem brain of ASD 118 …”
Section: Potential Pathogenesis Of Asdmentioning
confidence: 99%
“…125 A mechanistic modeling based on transcriptome suggested a direct link between inflammation and ASD in neurons. 118 Notedly, the MIA is a one of the common environmental risk factors of ASD pathology during pregnancy. [126][127][128] The adaptive immune pathway was enriched in maternal blood from mothers of children later diagnosed with ASD by transcriptome.…”
Section: Othersmentioning
confidence: 99%
See 2 more Smart Citations
“…The cause of this has not been identified despite detailed clinical investigations. Parallel to the age‐related increase in the E:I cortical balance in individuals with SSADH deficiency, a recent study examining post‐mortem brains demonstrates that individuals with ASD lose GABAergic (inhibitory) cortical tone as they age through adolescence into adulthood 5 . Thus, the age‐related effect seen in SSADH deficiency may be a helpful model for the age‐related changes in other neurodevelopmental disorders across the lifespan.…”
mentioning
confidence: 99%